Validation of a quality assessment tool for insurance services in business-to-business marketing - Nicolae Al. Pop; Carmen Petrisoaia (The International Journal of Management Science and Information Technology (IJMSIT), 2013)
Considering their importance and place in the production of the GDP (Gross domestic product), services are regarded by academicians and practitioners as a key element in shaping the competitiveness of the national economy. Service quality drives the growth and progress of any company. Insurance services in Romania are an active market, with a high development potential. The objectives of this article are closely related to the validation of a set of assessment tools, which allow accurate quality assessment of insurance services by using the measurement scale previously developed by Vandaele ðsi Gemmel for the business-to-business environment. The authors of this article aimed at testing this measurement scale by using a quantitative exploratory marketing research and a questionnaire addressed to company managers who have worked at least once with an insurance broker. Some of the dimensions used in the original measurement scale were not kept upon completion of the exploratory and confirmatory analysis. In conclusion, the study advocates the systematic use of such assessment tools in the insurance industry for the proper adaptation of the insurers' offer to the actual requirements of companies in this field.
Keywords: 650; service quality; measurement scales; insurance broker; organisational customers